(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2010)
On the basis of emotionally-expressive features of the names own differentiated emotionally neutral and a proprial vocabulary is emotionally painted; the last can have positive or negative connotation. Emotionally expressive signs taken away foremost show up in the colloquial, artistic and publicist broadcasting.